Revolutionizing Maxillofacial Regeneration Strategies: The Role of Scaffolds in Temporomandibular Joint and jawbone reconstruction - Qian Kai (BIO Web of Conferences)
For the repair of maxillofacial bone defects, traditional surgical methods result in slow healing and often require a second surgery to remove implants. To promote of jawbone and temporomandibular joint (TMJ) regeneration, scaffolds capable of delivering cells and growth factors that stimulate bone and cartilage development have become a recent focus in the field of tissue engineering. This paper provides a comprehensive review of scaffold applications in oral and maxillofacial regeneration, detailing the commonly utilized scaffolds, the cells they load (such as stem cells and macrophages) and the associated bioactive factors that promote growth, angiogenesis, and osteogenesis. Scaffolds (hydrogels, bioceramics, etc.) can facilitate the repair of jawbone injuries and preservation of post-extraction socket sites. Moreover, multi-layer composite hydrogel scaffolds have the potential to simultaneously promote the regeneration of bone, cartilage, and the articular disc, offering a therapeutic approach for temporomandibular joint disorders. This review provides clinicians with scientific evidence and guidance in selecting appropriate scaffolds for different clinical situations.